Metformin treatment and gastrointestinal symptoms in youth: Findings from a large tertiary care referral center. Issue 2 (3rd December 2020) - Meyers, Abby G.; Hudson, Jennifer; Cravalho, Celeste K. L.; Matta, Samantha T.; Villalobos‐Perez, Alfredo; Cogen, Fran; Chung, Stephanie T.
Abstract: Objectives: Metformin is the only oral therapy for youth with type 2 diabetes, but up to 50% require additional agents within 2 years of diagnosis. Extended‐release (XR) metformin formulations may improve adherence and tolerability–important mediators of treatment response–but data in youth is lacking. To evaluate rates of gastrointestinal (GI) symptoms in patients treated with metformin (SR and XR) and the change in GI symptoms after changes in metformin therapy. Research Design and Methods: Retrospective chart review of youth with Type 2 or prediabetes seen in a multidisciplinary clinic during 2016–2019. Results: Of 488 eligible patients, 41.4% and 21.1% were taking metformin SR and XR respectively, with most (58%, n = 178/305) taking a total daily dose of ≥1500 mg/day. Those not on metformin tended to be younger, leaner, and had lower HbA1cs than those taking metformin, p < 0.05. Thirty percentage of patients described GI symptoms, most commonly, abdominal pain and diarrhea. There was no difference in GI symptoms in those on SR versus XR (18.3% vs. 14.6%, p = 0.41). Among patients who initiated metformin, rates of GI symptoms increased (13%–33%, p = 0.001, n = 99), while rates tended to decrease when metformin was discontinued (28%–12%, p = 0.076, n = 50). Rates of GI symptoms were unchanged among those that switched from SR to XR metformin (17% vs. 14%, p = 0.6, n = 58). Conclusions: GI symptoms are common in youth with type 2 diabetes taking metformin XR and SR. Adjuncts to mitigate GI symptoms in youth on metformin therapy are needed to improve quality of life and medication adherence.